Adaptive sliding mode control and observation. Issue 9 (1st September 2016) - Shtessel, Yuri; Fridman, Leonid; Plestan, Franck
ABSTRACT: This editorial article gives a short introduction to Special Issue of International Journal of Control on Adaptive Sliding Mode Control and Observation.